Peace of mind: A pilot community-based program for older adults with memory loss - Buettner, PhD, CTRS, FGSA, Linda L. (American Journal of Recreation Therapy, 2012)
This pilot project was established to refine and test the Community of Care continuum for older adults with memory loss. The treatment group (n = 40) received the opportunity to select classes and was compared to the control group (n = 40), members of which simply maintained their normal lifestyles in the community after assessment. A total of 80 participants were tested at baseline, six months, and 12 months. Data were analyzed using repeated-measure analysis of variance to assess the effectiveness of the intervention over time. This allowed for analysis regarding intervention, time, and the interactive effects of time and intervention. The treatment group showed significant positive intervention effects (p < 0.05) for Mini-Mental State Examination (MMSE), Geriatric Depression Scale (GDS), instrumental activities of daily living (IADL), and quality of life. These preliminary findings show great promise for recreation therapists and others using community-based programs for older adults concerned about memory loss.